Semantic imaging features predict disease progression and survival in glioblastoma multiforme patients Semantische Bildeigenschaften prognostizieren Tumorprogression und Überleben von Patienten mit Glioblastoma multiforme - Peeken, Jan C.; Hesse, Josefine; Haller, Bernhard; Kessel, Kerstin A.; Nuesslin, Fridtjof; Combs, Stephanie E. (Strahlentherapie und Onkologie, 2018)
Background: For glioblastoma (GBM), multiple prognostic factors have been identified. Semantic imaging features were shown to be predictive for survival prediction. No similar data have been generated for the prediction of progression. The aim of this study was to assess the predictive value of the semantic visually accessable REMBRANDT [repository for molecular brain neoplasia data] images (VASARI) imaging feature set for progression and survival, and the creation of joint prognostic models in combination with clinical and pathological information. Methods: 189 patients were retrospectively analyzed. Age, Karnofsky performance status, gender, and MGMT promoter methylation and IDH mutation status were assessed. VASARI features were determined on pre- and postoperative MRIs. Predictive potential was assessed with univariate analyses and Kaplan–Meier survival curves. Following variable selection and resampling, multivariate Cox regression models were created. Predictive performance was tested on patient test sets and compared between groups. The frequency of selection for single variables and variable pairs was determined. Results: For progression free survival (PFS) and overall survival (OS), univariate significant associations were shown for 9 and 10 VASARI features, respectively. Multivariate models yielded concordance indices significantly different from random for the clinical, imaging, combined, and combined + MGMT models of 0.657, 0.636, 0.694, and 0.716 for OS, and 0.602, 0.604, 0.633, and 0.643 for PFS. “Multilocality,” “deep white-matter invasion,” “satellites,” and “ependymal invasion” were over proportionally selected for multivariate model generation, underlining their importance. Conclusions: We demonstrated a predictive value of several qualitative imaging features for progression and survival. The performance of prognostic models was increased by combining clinical, pathological, and imaging features.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Biomarker; Prognostic model; Radiomics; Semantic features; VASARI